2017
DOI: 10.1007/s11356-017-9113-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of low-temperature combustion and dimethyl ether-diesel blends on performance, combustion, and emission characteristics of common rail diesel engine: a CFD study

Abstract: Due to presence of more oxygen, absence of carbon-carbon (C-C) bond in chemical structure, and high cetane number of dimethyl ether (DME), pollution from DME operated engine is less compared to diesel engine. Hence, the DME can be a promising alternative fuel for diesel engine. The present study emphasizes the effect of various exhaust gas recirculation (EGR) rates (0-20%) and DME/Diesel blends (0-20%) on combustion characteristics and exhaust emissions of common rail direct injection (CRDI) engine using three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 24 publications
3
4
0
Order By: Relevance
“…Soudagar et al [45] reported that the oxygenated ternary blends showed a promising reduction in BSFC which is attributed to reducing viscosity and density, thus improving spray characteristics, and further combustion properties are enhanced. Other studies found similar results [11,35].…”
Section: Combustion Characteristicssupporting
confidence: 67%
See 2 more Smart Citations
“…Soudagar et al [45] reported that the oxygenated ternary blends showed a promising reduction in BSFC which is attributed to reducing viscosity and density, thus improving spray characteristics, and further combustion properties are enhanced. Other studies found similar results [11,35].…”
Section: Combustion Characteristicssupporting
confidence: 67%
“…As a result, BTE is improved. The results were correlated with a few journal articles [25,35,41]. International Journal of Energy Research than standard diesel owing to lower calorific value and higher viscosity [42].…”
Section: Combustion Characteristicssupporting
confidence: 66%
See 1 more Smart Citation
“…In order to get an accurate assessment of the changes in emission levels with CDA operation, a three-dimensional CFD model for the combustion chamber of the diesel engine D-49 was constructed in software FIRE ESE DIESEL, allowing to perform model settings, injection, and combustion analysis in diesel engines reliably and accurately [52]. In the diesel engine D-49, the injector with ten nozzles is placed centrally over the top of the piston.…”
Section: D Engine Combustion Modelmentioning
confidence: 99%
“…Even if the current solution implies the use of a small quantity of diesel -that anyway represents under 10% of the total amount of fuel supplied to the cylinder -for future solution the diesel fuel could be replaced with renewable solutions like dimethylether, which has been proved by many researchers to be a viable solution for diesel [2][3][4][5]. A survey of the available literature has showed that there are numerous studies about the use of ethanol fumigation [6][7][8][9] and diesel-ethanol blends [10][11][12][13][14][15], but very few studies that cover such a process that involves a separate direct injection of both fuels (diesel and ethanol), in which the diesel pilot injection is used to create the required conditions for the autoignition of a main ethanol injection, which is believed to be due to its higher complexity.…”
Section: Introductionmentioning
confidence: 99%